Food choice and food consumption frequency of Cape Verde inhabitants - Cabral, D (2019)
The knowledge of the food pattern of a population is crucial for establishing nutritional and epidemiological profiles, as well as for controlling the market of foodstuffs and to help in the management of stock of staple foods. This study aims to evaluate food consumption and its association with the underlying motives for consumers' food choices, through the application of a Food Frequency Questionnaire (FFQ) followed by a Food Choice Questionnaire (FCQ). Face to face interviews were conducted with 503 participants, recruited at their homes, workplaces, health centers and other central locations in Cape Verde, only including subjects aged 18 years, without a self-reported history of chronic diseases. Food frequency analysis, as well as exploratory factorial analysis (EFA) were used to determine dietary patterns and nonparametric statistical tests for comparisons and associations of variables. The EFA yielded 4 patterns termed as: "Traditional", "Western", "Balanced" and "Energetic". Using an FCQ structure of 9 factors, three different groups were obtained from hierarchical clustering. (Cabral, de Almeida, & Cunha, 2017). The results show that Cape Verdean inhabitants follow global diet trends (towards the so-called "westernization"), however, in a more moderate rate if compared to other developing country populations. Consuming "junk food" is infrequent in Cape Verde, which appears to be due to limited availability and accessibility of this type of food. The rural coastal population remains more attached to traditional foods, consuming local products and traditional dishes, whereas in the urban population, one may notice the "westernization" of consumption. The application of an FFQ in combination with the FCQ provided in-depth information on eating attitudes and behaviors.